Optimalisasi Pemanfaatan Perencanaan Tata Ruang Bagi Pengembangan Aktivitas Paralayang Kabupaten Sumedang - Ryan Ryan; Zefri Zefri; Soekmana Soma (Jurnal Kajian Wilayah dan Kota, 2022)
The development of the tourism sector has an unlimited positive impact on regional economic income. Sumedang as one of the districts located in West Java Province is a district with a dominance of hilly and mountainous morphology. This condition results in several locations in Sumedang Regency having water difficulties so that a lot of land is not optimally utilized for agriculture. This less than optimal land from the agricultural side turns out to have no small potential for tourism development, especially paragliding special interest sports tourism. This type of research is descriptive qualitative which aims to describe the extent to which spatial planning policies in Sumedang Regency have accommodated the sustainability of paragliding tourism. Spatially, the analysis uses map instruments as part of the Regional Apparatus Organization (OPD) spatial policy. The support of the spatial planning sector for the continuity of paragliding potential in Sumedang Regency is still not optimal, this can be seen through existing spatial planning in locations around Kampung Toga. Spatial control and restrictions on building intensity have not been fully planned in order to preserve the potential of paragliding in Sumedang Regency